The E3-ligase Siah2 activates mitochondrial quality control in neurons to maintain energy metabolism during ischemic brain tolerance - Maria Josè Sisalli; Elena D’Apolito; Ornella Cuomo; Giovanna Lombardi; Michele Tufano; Lucio Annunziato; Antonella Scorziello (Cell Death and Disease)
Abstract Mitochondrial quality control is crucial for the homeostasis of the mitochondrial network. The balance between mitophagy and biogenesis is needed to reduce cerebral ischemia-induced cell death. Ischemic preconditioning (IPC) represents an adaptation mechanism of CNS that increases tolerance to lethal cerebral ischemia. It has been demonstrated that hypoxia-induced Seven in absentia Homolog 2 (Siah2) E3-ligase activation influences mitochondrial dynamics promoting the degradation of mitochondrial proteins. Therefore, in the present study, we investigated the role of Siah2 in the IPC-induced neuroprotection in in vitro and in vivo models of IPC. To this aim, cortical neurons were exposed to 30-min oxygen and glucose deprivation (OGD, sublethal insult) followed by 3 h OGD plus reoxygenation (lethal insult). Our results revealed that the mitochondrial depolarization induced by hypoxia activates Siah2 at the mitochondrial level and increases LC3-II protein expression, a marker of mitophagy, an effect counteracted by the reoxygenation phase. By contrast, hypoxia reduced the expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), a marker of mitochondrial biogenesis, whereas its expression was increased after reoxygenation thus improving mitochondrial membrane potential, mitochondrial calcium content, and mitochondrial morphology, hence leading to neuroprotection in IPC. Furthermore, Siah2 silencing confirmed these results. Collectively, these findings indicate that the balance between mitophagy and mitochondrial biogenesis, due to the activation of the Siah2-E3-ligase, might play a role in IPC-induced neuroprotection.